Tinjauan Yuridis Pelaksanaan Pemutusan Hubungan Kerja Secara Sepihak oleh Perusahaan Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan (Studi Kasus Putusan Mahkamah Agung Republik Indonesia Nomor 277 K/Pdt.Sus-Phi/2017) - Putri Andini; Reny Septiani (Fakultas Hukum, Universitas Internasional Batam, 2019)
Termination of employment should not be carried out unilaterally or arbitrarily, because termination of employment occurs due to certain reasons that cause a worker to escape from a work agreement and responsibility as long as he is bound by a work agreement from the company where he works. But in its implementation there are still many unilateral termination of employment. The purpose of this study is to analyze the legal protection of workers who are unilaterally terminated by the company and analyze the judges' consideration of cases of unilateral termination based on the Decision of the Supreme Court Number 277 / K / Pdt.Sus-PHI / 2017. The research methodology used is normative juridical. Normative juridical research uses primary, secondary and tertiary legal materials and uses primary data. To obtain the data used library study methods and interviews. The approach used in this study is the case approach and the legal approach. Based on the research that has been done, it is found the legal fact that the unilateral termination of employment is not permitted by the company. Termination of employment must obtain a determination from an indutrial relationship dispute settlement institution and Law No. 13 of 2003 has provided legal protection for workers in accordance with the theory of legal protection proposed by Philipus M. Hadjon. In addition, the Supreme Court of the Republic of Indonesia in Decision Number 277 K / Pdt.Sus-PHI / 2017 has decided the case in accordance with the provisions in the legislation.